«Il tracciato della limaccia»: note per uno studio genetico-variantistico di Questo muro (1973) di Franco Fortini - Niccolai, Elena (L'ospite ingrato, 2025)
This study reexamines the caesura represented by Questo muro (1973) in Fortini’s production. Against the traditional interpretation that reads it as an intimist withdrawal, the variantistic investigation reveals a compositional process oriented toward allegorical universalization. The analysis documents two directions: the progressive elimination of autobiographical elements in favor of a denotative-allegorical lexicon and the search for metrical-syntactic verticality through verse-sentences and parataxis. The comparison with Sereni’s practice highlights by contrast the specificity of Fortini’s project: where Sereni adds temporal deictics, Fortini systematically eliminates them to remove the text from referential contingency.